# Solve Using the Square Root Property 7x^2+4x-12=44-37x 7×2+4x-12=44-37x
Move all terms containing x to the left side of the equation.
Add 37x to both sides of the equation.
7×2+4x-12+37x=44
7×2+41x-12=44
7×2+41x-12=44
Move 44 to the left side of the equation by subtracting it from both sides.
7×2+41x-12-44=0
Subtract 44 from -12.
7×2+41x-56=0
Factor by grouping.
For a polynomial of the form ax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=7⋅-56=-392 and whose sum is b=41.
Factor 41 out of 41x.
7×2+41(x)-56=0
Rewrite 41 as -8 plus 49
7×2+(-8+49)x-56=0
Apply the distributive property.
7×2-8x+49x-56=0
7×2-8x+49x-56=0
Factor out the greatest common factor from each group.
Group the first two terms and the last two terms.
(7×2-8x)+49x-56=0
Factor out the greatest common factor (GCF) from each group.
x(7x-8)+7(7x-8)=0
x(7x-8)+7(7x-8)=0
Factor the polynomial by factoring out the greatest common factor, 7x-8.
(7x-8)(x+7)=0
(7x-8)(x+7)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
7x-8=0
x+7=0
Set the first factor equal to 0 and solve.
Set the first factor equal to 0.
7x-8=0
Add 8 to both sides of the equation.
7x=8
Divide each term by 7 and simplify.
Divide each term in 7x=8 by 7.
7×7=87
Cancel the common factor of 7.
Cancel the common factor.
7×7=87
Divide x by 1.
x=87
x=87
x=87
x=87
Set the next factor equal to 0 and solve.
Set the next factor equal to 0.
x+7=0
Subtract 7 from both sides of the equation.
x=-7
x=-7
The final solution is all the values that make (7x-8)(x+7)=0 true.
x=87,-7
Solve Using the Square Root Property 7x^2+4x-12=44-37x     